2006
DOI: 10.1093/ptj/86.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Comparing 2 Versions of the Chedoke Arm and Hand Activity Inventory With the Action Research Arm Test

Abstract: Background and Purpose. The Chedoke Arm and Hand Activity Inventory (CAHAI) is a new, validated upper-limb measure that uses a 7-point quantitative scale in order to assess functional recovery of the arm and hand after a stroke. The purposes of this study were: (1) to determine whether the longitudinal validity of scores on 2 versions of a new upper-limb measure, the CAHAI (CAHAI-9 and CAHAI-13), was greater than that of scores on the Action Research Arm Test (ARAT) and (2) to determine whether the cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 16 publications
0
30
0
3
Order By: Relevance
“…In this study, the tasks of IADL identified as being more frequent were holding a light object and using the remote control of the TV/tablet/cellular, being the first task most performed with the paretic UL, contemplated in TEMPA (MICHAELSEN et al, 2008). Nevertheless, the second activity involves some movement components of the task of typing on a telephone of the CAHAI instrument (BARRECA et al, 2006), which requires greater manual and digital skills. However, this task was performed primarily with non-paretic UL.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…In this study, the tasks of IADL identified as being more frequent were holding a light object and using the remote control of the TV/tablet/cellular, being the first task most performed with the paretic UL, contemplated in TEMPA (MICHAELSEN et al, 2008). Nevertheless, the second activity involves some movement components of the task of typing on a telephone of the CAHAI instrument (BARRECA et al, 2006), which requires greater manual and digital skills. However, this task was performed primarily with non-paretic UL.…”
Section: Discussionmentioning
confidence: 76%
“…Regarding the assessment instruments with a greater number of tasks similar to IADL, the MAL, MAM-36 and now TEMPA are highlighted again, considering that the instruments of perceived performance usually bring a greater number of evaluated items and consequently, they can have a greater chance of representing more tasks performed in the home environment. However, both TEMPA and CAHAI are instruments that stand out because they have relevant tasks and, although they require different materials and a trained evaluator for their application, they are simple tasks to be carried out in daily life (BARRECA et al, 2006;CHEN;BODE, 2010;MICHAELSEN et al, 2008;PEREIRA et al, 2012;SALIBA et al, 2011). In TEMPA, the number of tasks contemplated exceeded the number of tasks evaluated in the instrument, because the tasks evaluated are sequential, that is, they involve several actions within the same task, such as the task of taking a jar, serving water and carrying the glass to the mouth (MICHAELSEN et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations